2013
DOI: 10.1017/s2045796013000437
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction and psychopathology in a community before and during an economic crisis

Abstract: Background. Internet addiction disorder (IAD) is a novel concept under scrutiny for a definite inclusion in the psychiatric taxonomy, after showing correlations with overt expressions of psychopathology. This study aims to assist the scientific dialogue concerning IAD while presenting comparative data on adolescent psychopathology before and during a major economic crisis that has affected Greece from 2010 onwards. Methods. This is a cross-sectional study of a high school student population, aged 12-18, on IAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
8
0
5
Order By: Relevance
“…These trauma‐related emotional responses are risk factors for the development of addictive behaviors and relapse, including substance and behavioral addictions 13 . Disasters, such as massive accident disasters and economic crises, have increased rates of Internet addiction, especially among adolescents 14,15 . When exposed to stressful or traumatic events, adolescents who have dysfunctional coping abilities are more prone to develop Internet addiction 16 .…”
Section: Introductionmentioning
confidence: 99%
“…These trauma‐related emotional responses are risk factors for the development of addictive behaviors and relapse, including substance and behavioral addictions 13 . Disasters, such as massive accident disasters and economic crises, have increased rates of Internet addiction, especially among adolescents 14,15 . When exposed to stressful or traumatic events, adolescents who have dysfunctional coping abilities are more prone to develop Internet addiction 16 .…”
Section: Introductionmentioning
confidence: 99%
“…3 With the increasing infiltration of the Internet into daily life, psychopathological symptoms of Internet addiction have also been observed in recent years. 4 Specifically, some psychiatrists have proposed that Internet gaming disorders should be classified under substance abuse and addictive disorders in the revised Diagnostic and Statistical Manual of Mental Disorders (DSM-5). 5 For instance, Internet game addicts have cravings that are similar to smokers.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most empirical studies have found a positive association between problematic internet use (PIU) and psychopathological symptoms both in normal samples of adolescents [1][2][3][4][5] and adults [6][7][8][9][10][11]. A few studies have examined this relationship among clinical samples (i.e., among diagnosed internet addicts), comparing them to healthy control groups [2,12,13] or clinical control groups [14,15].…”
Section: Introductionmentioning
confidence: 99%